Clinical Incidence and Characteristics of Newly Diagnosed Type 1 Diabetes in Chinese Children and Adolescents: A Nationwide Registry Study of 34 Medical Centers - Li, Guo-Hua; Huang, Ke; Dong, Guan-Ping; Zhang, Jian-Wei; Gong, Chun-Xiu; Luo, Fei-Hong; Luo, Xiao-Ping; Wang, Chun-Lin; Zhu, Min; Li, Pin; Wang, Ling; Fu, Jun-Fen; et al. (Frontiers in Pediatrics, 2022)
Objective: To investigate the incidence and characteristics of T1DM of children and adolescents in China. Methods: Data on all pediatric patients with newly diagnosed T1DM was retrospectively collected from 34 medical centers in China from January 2015 to January 2020. Patients were classified into three age groups: <5 years, 5 to <10 years, and ≥10 years of age. The same patient population was also categorized into DKA and non-DKA group based on clinical criteria. Results: The mean annual incidence of T1DM was 3.16/100,000 during years 2015-2019. A total of 6544 patients with newly diagnosed T1DM aged 0-16 years (median 7.84±3.8) were studied [ages <5 years (29.3%), 5 to <10 years (38.7%), and ≥10 years (32%)], 41.8% of them had measurable T1DM-related antibodies and 52.7% had DKA. Among all three age groups, the <5 years group had the lowest BMI z score and CP, while it had the highest incidence rate of DKA (56.9%). Comparing to the non-DKA group, the DKA group were significantly younger, with lower BMI z score and CP, higher antibody positive rate, HbA1c and the rate of insulin pump therapy. Conclusion: The clinical incidence of T1DM of children and adolescents in China was 3.16/100,000. Patients with DKA at the first diagnosis of T1DM have a worse β-cell function. Public health measures for the prevention and treatment of T1DM should focus on preschoolers. More efforts should be dedicated to early screening and diagnosis of the T1DM.